Applying Semantic Web Services to Enterprise Web. (2nd February 2012) - Hu, Yang; Yang, Qingping; Sun, Xizhi; Wei, Peng
Enterprise web provides a convenient, extendable, integrated platform for information sharing and knowledge management. However, it has to deal with the increasing complexity, heterogeneity and amount of information processed. This paper proposes to use Semantic Web Services (SWSs) to add higher level of semantic functionalities to current enterprise webs, enhancing their usability and usefulness. This paper explores the use of SWSs in enterprise web and discusses SWSs approach for designing enterprise web applications. An SWS-oriented model is presented with resources and services described by ontology and processed through SWS, resulting in integrated administration, interoperability and automated reasoning.